2021
DOI: 10.1109/jtehm.2021.3069353
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Smart Hallway for Marker-Less Human Foot Tracking and Stride Analysis

Abstract: In this research, a marker-less 'smart hallway' is proposed where stride parameters are computed as a person walks through an institutional hallway. Stride analysis is a viable tool for identifying mobility changes, classifying abnormal gait, estimating fall risk, monitoring progression of rehabilitation programs, and indicating progression of nervous system related disorders. Methods: Smart hallway was build using multiple Intel RealSense D415 depth cameras. A novel algorithm was developed to track a human fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Intriguingly, despite having an older production age, both Kinect 1 and 2 seem to rival RealSense's signal quality and capture range during walking (Mejia-Trujillo et al, 2019). Moreover, temporal parameters seem to exhibit slightly better accuracy when recorded with RealSense, whereas spatial parameters retain similar values to Kinect measurements (Gutta et al, 2021). While a few gait studies with Intel's RealSense exist, up to the present moment no publications known to the authors have used the technology to assess gait and balance explicitly in either PD or MS patient groups.…”
Section: Intel Realsensementioning
confidence: 96%
“…Intriguingly, despite having an older production age, both Kinect 1 and 2 seem to rival RealSense's signal quality and capture range during walking (Mejia-Trujillo et al, 2019). Moreover, temporal parameters seem to exhibit slightly better accuracy when recorded with RealSense, whereas spatial parameters retain similar values to Kinect measurements (Gutta et al, 2021). While a few gait studies with Intel's RealSense exist, up to the present moment no publications known to the authors have used the technology to assess gait and balance explicitly in either PD or MS patient groups.…”
Section: Intel Realsensementioning
confidence: 96%
“…As a versatile system for relatively inexpensive markerless human body tracking using a depth sensor, Kinect v2 has been used in the gait analysis [ 14 , 15 , 16 ]. In addition, several markerless motion capture systems applying 3D optical sensing technology were reported in 2021 [ 17 , 18 , 19 ]. Baak et al developed a tool for real-time 3D full-body pose estimation from 2.5-dimensional depth images using some pose databases [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Buker et al reported High-Resolution Depth Net (HRDepthNet) model which retrains the original HRNet for depth images using a convolutional neural network [ 18 ]. Gutta et al reported a markerless foot tracking system, although their system needs six temporally and spatially synchronized cameras to capture depth and color and an 8 × 6 chessboard as a reference coordinate system on the floor plane [ 19 ]. However, these systems are complicated to prepare and lack versatility, so they are not widespread in general practice.…”
Section: Introductionmentioning
confidence: 99%